2017
DOI: 10.1509/jm.14.0089
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Effects of Ex Ante Contractual Completeness and Ex Post Governance on Compliance in Franchised Marketing Channels

Abstract: This study examines the heretofore neglected joint effects of ex ante contractual completeness and ex post governance on compliance in a franchise setting. In contrast to much of the extant literature that views contractual completeness in the aggregate, the present research disaggregates contractual completeness into ex ante monitoring and enforcement completeness, and additionally distinguishes between ex post monitoring and enforcement, allowing for a nuanced examination of the joint effects of different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 129 publications
8
86
0
Order By: Relevance
“…First, we extend the interorganizational contracting literature (e.g., Carson and Ghosh 2019; Dean, Griffith, and Calantone 2016; Kashyap, Antia, and Frazier 2012; Kashyap and Murtha 2017; Lusch and Brown 1996) by introducing the concept of contract ambiguity from the law literature, bringing forth the likely strategic role contract ambiguity plays in governing business transactions. This advances the literature in that although legal scholars recognize contract ambiguity’s prevalence and substantive impact on relationships (e.g., Choi and Triantis 2008, 2010; Drahozal and Hylton 2003; Scott and Triantis 2006), marketing scholars have yet to investigate this topic.…”
Section: Discussionmentioning
confidence: 99%
“…First, we extend the interorganizational contracting literature (e.g., Carson and Ghosh 2019; Dean, Griffith, and Calantone 2016; Kashyap, Antia, and Frazier 2012; Kashyap and Murtha 2017; Lusch and Brown 1996) by introducing the concept of contract ambiguity from the law literature, bringing forth the likely strategic role contract ambiguity plays in governing business transactions. This advances the literature in that although legal scholars recognize contract ambiguity’s prevalence and substantive impact on relationships (e.g., Choi and Triantis 2008, 2010; Drahozal and Hylton 2003; Scott and Triantis 2006), marketing scholars have yet to investigate this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Agency theory is concerned with circumventing problems that can arise during the initiation, ongoing and termination stages of an agency relationship (Heide, 1994) by applying ex ante and/ or ex post governance procedures (Eisenhardt, 1989). However, most of the literature that has so far drawn on agency theory has explored governance based either on the ex ante formal contract or on the ex post relationship (for exceptions, see Poppo and Zhou, 2014;Kashyap et al, 2012;Kashyap and Murtha, 2017;Mooi and Gilliland, 2013). To the best of our knowledge, no study on purchasing considered that the relationship originates in, and then builds on, an ex ante social contract.…”
Section: The Link Between Contracting and Contract Managementmentioning
confidence: 99%
“…Research linking contracting and contract management to performance is very limited (Kashyap et al, 2012;Kashyap and Murtha, 2017). Kashyap et al (2012) showed that ex ante contractual completeness leads to less ex post monitoring during contract management.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in cultures, languages, and knowledge of the operating environments (Aulak and Gençturk, 2008; Prieto et al, 2009) affect international exchange relationships (Batonda and Perry, 2003) because they make trust building more complex (Geyskens et al, 1996). Knowledge and understanding of the cultural context also affect how contracts are interpreted by channel members (Bamberger, 2008; Heide et al, 2014) and how they respond to monitoring and enforcement efforts of their exchange partners (Heide et al, 2007; Kashyap and Murtha, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%